Pengaruh Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) dan Pajak Bumi Bangunan Perdesaan dan Perkotaan (PBB-P2) Terhadap Pendapatan Asli Daerah DKI Jakarta Tahun 2017 – 2022 - Oktavi Yanti, Putri Faraz; Suhono, Suhono (Jurnal Ilmiah Wahana Pendidikan, 2024)
The point of this study is to ascertain and examine the effect of Land and Building Tax and Acqustion Duty of Right on Land and Building both partially and simultaneously on DKI Jakarta's Original Local Government Revenue in 2017 – 2022. The population of this study includes data recapitulation targets and PBB-P2 and BPHTB revenues in 2017 – 2022. Through the use of purposive sampling, the sample was selected.. Associative quantitative is the method of data analysis used in this study. t and f tests for testing hypotheses. The outcames of this study show that BPHTB (X1) has a significant positive effect on PAD DKI Jakarta. This is indicated by a significance value (Sig.) 0.011 < 0.05. PBB-P2 (X2) has a negative significant effect on PAD DKI Jakarta. This is indicated by a significance value (Sig.) 0.019 < 0.05. BPHTB (X1) and PBB-P2 (X2) have a simultaneous effect on PAD DKI Jakarta. This is indicated by a significance value (Sig.) 0.032 < 0.05.